Formation Of Tolerance In The Upcoming Generation Within The Family Nurturing System - Zhazykova, Makpal; Kozhayeva, Sanim; Medeubayeva, Kenzhekhan; Tumenbayeva, Assel; Salima Seitenova, Gulim Yeleussinova, (Opción, 2019)
The aim of the study is to investigate the formation of tolerance in the upcoming generation within the family nurturing system via comparative qualitative research methods and historical analysis. As a result, the parents of indifferent style take no part in the process of their children nurturing, they perceive child with emotional coldness, the requirements and interests of children are simply ignored. In conclusion, it is impossible to force people to think equally, to trust equally, to work equally, and to have a rest equally. There is an only consensus - the respectful attitude towards people